Pengaruh Review Beauty Vlogger Dan Kualitas Produk Terhadap Keputusan Pembelian Produk Skincare Ms. Glow Dalam Perspektif Ekonomi Islam - Anisa Ade Novalinda; Nurhayati Nurhayati (BADAN PENERBIT STIEPARI PRESS, 2024)
: The abundance of skincare products in Indonesia is due to the high enthusiasm of consumers regarding current skincare developments. In sales data for the best-selling skincare products on Shopee and Tokopedia in 2021-2022, MS.Glow experienced a significant decrease in purchases compared to other brands,namely Somehinc and Scarlett Whitening. because consumers are starting to have choices. This research uses a quantitative approach method. The data used is primary data taken by distributing questionnaires online via Google form to MS.Glow consumers at the Ayudy Beauty Store. The sample used was 70 people. The data analysis used was using validity tests, r reliability tests, classical assumption tests, and hypothesis tests which were processed using SPSS version 21. The results of this research show that the variable beauty vlogger review has no positive and insignificant effect on purchasing decisions, the product quality variable has a positive and significant effect on purchasing decisions,beauty vlogger review and product quality in improving purchasing decisions for Ayudy Beauty Store consumers must be based on Islamic religious principles.